Główne podejścia teoretyczne do analizy „kolorowych rewolucji” na obszarze postradzieckim: Theoretical approaches to the analysis of ‘colour revolutions’ in post-Soviet space - Hurska-Kowalczyk, Liana (Przegląd Wschodnioeuropejski, 2021)
The objective of this article is an overview and analysis of three theoretical approaches applied to ‘colour revolutions’ (wide anti-government protests in the area of the former ZSSR, which led to changes in governments), considered as 1) a way to re-activate the process of democratization in post-Soviet countries, based on Samuel P. Huntington’s concept of the waves of democracy (Valerie Bunce, Sharon Wolchik, Thomas Carothers, Mark Beissinger, Michael McFaul, Taras Kuzio); 2) the effect of the impact of structural factors (Lucan Way, Steven Levitsky, Katya Kalandadze, Mitchell Orenstein); 3) a method to transform “post-soviet neopatrimonial regimes”, founded on the paradigms of patronal politics (Henry Hale, Rałał Czachor, Vladimir Gel’man, Ołeksandr Fisun).